2016
DOI: 10.3389/fmicb.2016.00811
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Rearrangements and Functional Diversification of lecA and lecB Lectin-Coding Regions Impacting the Efficacy of Glycomimetics Directed against Pseudomonas aeruginosa

Abstract: LecA and LecB tetrameric lectins take part in oligosaccharide-mediated adhesion-processes of Pseudomonas aeruginosa. Glycomimetics have been designed to block these interactions. The great versatility of P. aeruginosa suggests that the range of application of these glycomimetics could be restricted to genotypes with particular lectin types. The likelihood of having genomic and genetic changes impacting LecA and LecB interactions with glycomimetics such as galactosylated and fucosylated calix[4]arene was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
1
27
0
2
Order By: Relevance
“…In addition, LecB is a tetramer with four fucose-binding sites, but UEA-1 is a dimer offering only two binding sites (35). It is also worth noting that the sequence of LecB varies slightly between different strains of P. aeruginosa (51,52). Since ligand binding among LecB variants is conserved, we expect that these LecB variants are utilized in similar ways as we reported here for LecB in the P. aeruginosa strain PAO1.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, LecB is a tetramer with four fucose-binding sites, but UEA-1 is a dimer offering only two binding sites (35). It is also worth noting that the sequence of LecB varies slightly between different strains of P. aeruginosa (51,52). Since ligand binding among LecB variants is conserved, we expect that these LecB variants are utilized in similar ways as we reported here for LecB in the P. aeruginosa strain PAO1.…”
Section: Discussionsupporting
confidence: 55%
“…LecB has been studied in detail using multivalent and small molecule approaches. Interestingly, the sequence of LecB differs among clinical isolates of this highly variable pathogen, with some mutations in close proximity to the carbohydrate binding site, but carbohydrate-binding function is preserved across all lectins investigated [ 42 43 ]. The glycopeptide dendrimer 13 ( Fig.…”
Section: Reviewmentioning
confidence: 99%
“…structures of glycan-binding proteins (for example, lectins, adhesins, haemagglutinins and viral capsid proteins) from various organisms including humans and pathogens have been extensively studied and represent the majority of the LNBcontaining structures in the PDB. The pathogens include a fungus (or yeast, Candida glabrata; Diderrich et al, 2015), a nematode (Toxascaris leonina; Hwang et al, 2016), a protist (Toxoplasma gondii; Garnett et al, 2009), bacteria (Helicobacter pylori, Shiga toxin-producing Escherichia coli and Pseudomonas aeruginosa; Moonens et al, 2012Moonens et al, , 2016Boukerb et al, 2016) and viruses (influenza virus, norovirus, rotavirus and polyomavirus; Vachieri et al, 2014;Choi et al, 2008;Liu et al, 2017;Stehle & Harrison, 1997). Eight PDB entries for enzymes contain the -LNB unit as part of their substrate (discussed below).…”
Section: Lnb Units In the Protein Data Bankmentioning
confidence: 99%
“…Complex crystal structures of plant lectin IV from the African shrub Griffonia simplicifolia with Le b tetrasaccharide (Delbaere et al, 1993), microneme protein 1 from a protozoan parasite (T. gondii) with 3-SLN (Garnett et al, 2009), galectin Tl-gal from a canine gastrointestinal nematode parasite (T. leonina) with LNT (Hwang et al, 2016) and the adhesin Epa6A domain from a fungal pathogen (C. glabrata) with LNB (Diderrich et al, 2015) have been reported. For bacterial glycan-binding proteins and lectins, several crystal structures, including those of the adhesin BabA from H. pylori, the fimbrial adhesin subunit FedF from Shiga toxin-producing E. coli and the LecB lectin from P. aeruginosa, complexed with Lewis and type-1 ABO(H) blood group antigens have been reported (Moonens et al, 2012(Moonens et al, , 2016Boukerb et al, 2016). PDB entry 5f9d for BabA contains the whole Le b heptasaccharide (Fig.…”
Section: Binding Proteins From Other Eukaryotes and Microbesmentioning
confidence: 99%